Affecting Factors on Community Based Mangrove Replantation Programs in Semarang Coastal Area - Bintang Septiarani; Reny Yesiana (Department of Urban and Regional Planning, Universitas Diponegoro, 2020)
Climate change is no longer seen as a natural process when it has been correlated with human behavior, especially from increasingly rapid development activities. In Semarang, climate change has been affecting people's activity, especially in the coastal area. Coastal communities that depend on coastal resources feel the effects of climate change. Fishers, mangrove farmers, and fishpond farmers are vulnerable groups to the impacts of climate change because the coastal resources in quality and quantity decrease and affect their lives. Stakeholders make efforts through mangroves rehabilitation programs all over the coastal line, including the community approach to increase the mangrove growth rate. However, mangrove seeds planted in Semarang coastal area have different levels of life and growth rate in each planting location. Based on Environmental Agency of Central Java Province data in 2013, 8,594.89 ha of 11,732 ha mangrove vegetation in the North Coast of Central Java Province are in damaged condition. Hence, this paper aims to elaborate on the key factors of community-based mangrove replantation affecting the mangrove growth in the Semarang coastal area. Five mangroves rehabilitation areas in Semarang namely in Kelurahan Mangkang Kulon, Mangkang Wetan, Mangunharjo, Tugurejo and Kelurahan Trimulyo are observed throughout 2015-2016. The results show that suitability between mangrove species and the location is very influential on mangrove growth rates in Semarang Coastal. The community effort in each location also becomes the external factor affecting the growth of mangroves in Semarang Coastal Area. By understanding the factors of mangrove growth rate on the community-based mangrove replantation, better results of mangrove replantation programs can be acquired in the future.